(untitled) (Journal of the College of Basic Education, 2022)
Conjugation is (non-separation from the two parties), unlike (Istilizam), which means (non-separation from one side). The (correlation) varies according to the diversity of the correlative elements, including (morphological correlative), which occurs between the meanings of (morphological forms) of words. And the correlation occurs between the meaning of the past tense and the meaning of the present tense, even if the verb is in the present tense of the receiver, provided that the occurrence is definitive. And if the command verb is formative, then the correlation occurs between the meaning of (to command), the meaning of (to attend), and the meaning of (to proceed); For the participation of the three in (definite occurrence). And if one of the two verbal forms denotes the meaning of (cause), and the other denotes the meaning of (result), then there is a morphological connection between them.